Randomised phase II study of cisplatin and 5-fluorouracil (5-FU) versus cisplatin alone in advanced squamous cell oesophageal cancer - Bleiberg, H; Conroy, T; Paillot, B; Lacave, A.J; Blijham, G; Jacob, J.H; Bedenne, L; Namer, M; De Besi, P; Gay, F; Collette, L; Sahmoud, T (European journal of cancer (1990), 1997)
Patients with measurable or evaluable locally advanced or metastatic squamous cell carcinoma of the oesophagus were treated with cisplatin (CDDP), 100 mg/m 2, combined with 5-fluorouracil (5-FU) at a dose of 1000 mg/m 2 as a continuous infusion from days 1–5 (Arm A) or with CDDP alone (Arm B). Cycles were repeated every 3 weeks. 92 patients were randomised centrally, 88 were eligible. The response rate was 35% (95% CI (confidence interval), 20–54%) in Arm A and 19% (95% CI, 8–35%) in Arm B. One complete response was observed in each arm. The median duration of survival was 33 weeks and 28 weeks for Arm A and Arm B, respectively. Haematological and non-haematological toxicities were more frequent and more severe in Arm A. The most prominent toxicities were grade 4 aplasia and septicaemia (2), meningeal haemorrhage (1), cerebrovascular accident (3) and ischaemia of the lower limbs (1) all occurring in Arm A. Overall, seven treatment-related deaths (16%) were observed in Arm A, none in Arm B. The severe side-effects induced by the combination suggest that, currently, no standard chemotherapy can be recommended for patients with advanced squamous cell oesophageal cancer.